Land Use and Agriculture: Pitfalls and Precautions on the Road to Net Zero - Reay, Dave S. (Frontiers in Climate, 2020)
Land use is a crucial sector in delivering enhanced carbon sequestration globally. At the same time food production is a major source of global greenhouse gas emissions. As pressure mounts for all nations to increase their levels of ambition under the Paris Climate Agreement, so the pressure to radically reduce emissions from the agriculture sector and enhance carbon sequestration in the land use sector also ramps up. This trend is most clearly evident in the drive for ‘net zero’ where unavoidable emissions, such as those from food production, are balanced by more sequestration via land use change. Here we examine some of the major risks, applicable safeguards, and potential pathways for agriculture and land use in realising net zero. Using the UK as an example we highlight the importance of governance, finance, skills, research & technology, and society in this transition. We conclude that successful land use policy for net zero will require extremely demanding levels of integration and spatial resolution, but that the research base to support this is fast-developing. We also invoke the Cancun safeguards as a basis on which a more sustainable and just transition to net zero might be based. Finally, we warn of unintended distortions to policy and markets if the drive for net zero is too blinkered.